The hippocampal commissure: a new finding at prenatal 3D ultrasound in fetuses with isolated complete agenesis of the corpus callosum. (16th July 2015) - Contro, E.; Nanni, M.; Bellussi, F.; Salsi, G.; Grisolia, G.; Sanz‐Cortès, M.; Righini, A.; Rizzo, N.; Pilu, G.; Ghi, T.
Abstract Objective The aim of this research was to determine the prevalence and sonographic appearance of the hippocampal commissure in fetuses with isolated complete agenesis of the corpus callosum by three‐dimensional neurosonography in the multiplanar mode. Methods This was a multicenter observational study. Stored volume datasets of fetuses with isolated complete agenesis of the corpus were retrospectively retrieved for analysis in three tertiary centers. The presence or absence of the hippocampal commissure was independently evaluated in the coronal and midsagittal planes by two operators. Postnatal follow‐up was obtained in all cases. Results From November 2007 to February 2013, 41 cases between 19 and 30 weeks of gestation were retrieved for analysis. The hippocampal commissure was visible in the coronal and sagittal planes in 27/41 (65.8%), absent or not clearly recognizable in the remaining 14 cases. The qualitative analysis of the two operators was concordant in 100% of cases. Conclusions In more than half of fetuses with complete callosal agenesis, the hippocampal commissure may be visualized at prenatal ultrasound. This is a residual interhemispheric connection, which in normal cases is hidden by the corpus callosum itself. Further research is needed to establish if this has an impact on postnatal outcome. © 2015 John Wiley & Sons, Ltd.